Case report: A pregnant woman with recurrent craniopharyngioma: surgical decision-making and doctor-patient bond - Shen, Ao; Min, Yue; He, Shuanghong; Zhou, Dongjie; Jiang, Shu; Zhou, Peizhi (Frontiers in Oncology, 2024)
Craniopharyngioma is a rare, benign tumor that originates from the pituitary stalk and extends along the pituitary-hypothalamic axis. It can have serious effects due to its location, affecting hormone regulation, vision, and other neurological functions. It is particularly rare and challenging to manage it during pregnancy due to the potential impacts on both maternal and fetal health, requiring careful, individualized treatment. We reported a 26-year-old pregnant woman at 27 weeks with recurrent craniopharyngioma who presented with worsening consciousness and hydrocephalus. Despite recommendations to terminate the pregnancy for tumor resection, she chose to continue. We performed an endoscopic endonasal tumor resection with pituitary transposition to preserve pituitary function, and at 32 weeks, she delivered a healthy baby via cesarean section. We provided a detailed account of the perioperative complications and their management, addressing endocrine, temperature, and fluid regulation challenges. Throughout the process, the medical team maintained open communication with the patient and her family, respecting their desire to continue the pregnancy and exemplifying patient-centered, compassionate care.